Association between first 24-h mean body temperature and mortality in patients with diastolic heart failure in intensive care unit: A retrospective cohort study - Xu, Hongyu; Xie, Yonggang; Sun, Xiaoling; Feng, Nianhai (Frontiers in Medicine, 2022)
Abstract Background: Body temperature(BT) had been used to evaluate outcome in patients of various diseases. This study was aimed to investigate the relationship between BT and mortality in patients with diastolic heart failure(DHF) in intensive care unit(ICU). Methods: This was a retrospectively cohort study of the Medical Information Mart for Intensive Care (MIMIC)-IV dataset. A total of 4153 patients with DHF were included. Primary outcomes were 28-day ICU mortality and in-hospital mortality. BT was entered in analyses both as a continuous variable and a categorical variable. According to the distribution of BT, patients were categorized into three groups (hypothermia BT<36.5◦C,normal 36.5◦C≤BT<37.5◦C, hyperthermia BT≥37.5◦C). Multivariate logistic regression was applied to explore the association between BT and outcomes. Results: The proportions of three groups were 23.6%,69.2% and 7.2%, respectively. As a continuous variable, each 1◦C increase in BT was associated with a 19% decrease in 28-day ICU mortality (OR 0.81,95% CI:0.67 0.98, p=0.031) and with a 20% decrease in in-hospital mortality (OR 0.8,95% CI 0.67 0.94, p=0.006). When BT was used as a categorical variable, hypothermia signiﬁcantly associated with both 28-day ICU mortality (OR 1.28, 95% CI 1.02 1.62, p=0.035) and in-hospital mortality (OR 1.28, 95% CI 1.05 1.56, p=0.013). No statistical differences were observed between 28-day ICU mortality and in-hospital mortality with hyperthermia after adjustments. Conclusion: First 24-h mean BT after ICU admission was associated with 28-day ICU mortality and in-hospital mortality in Patients with DHF. Hypothermia had significantly increased mortality while hyperthermia had not.